A Case of Pediatric Eyelid Laceration ec Unusual Foreign Body: Poster Presentation - Case Report - Resident - Olivia, Mokolensang Gabriella; Umboh, Roy; Umboh, Anne (Majalah Oftalmologi Indonesia, 2023)
Introduction : Eyelid lacerations refer to partial or full-thickness defects in the eyelid and constitute a significant subset of facial trauma which is often accompanied by other injuries including foreign bodies. Case Illustration : A 16-year-old boy was brought to the emergency department with a laceration and penetrating orbital injury in his right upper eyelid. On examination, there was a 4 cm x 0,5 cm upper eyelid laceration caused by tooth penetrating, CT scan revealed a high density foreign body measuring 1,5 cm x 0,5 cm in the right upper eyelid as deep as levator muscle and no globe injury. The patient underwent an emergency operation under general anesthesia, the foreign body was removed completely and the size of the foreign body was 2,6cm x 0,5cm. After the removal of the foreign body, debridement was performed and then sutured layer by layer. After surgery, he was treated with Tetanus prophylaxis, antibiotic, and analgetic. Discussion : Eyelid laceration is one of the most encountered ocular trauma, but needed to be evaluated and treated carefully. Although the rate of ocular foreign bodies found was low, it can lead to devastating ocular morbidities. After surgery and treatment, there is no other complaint from the patient. Visual acuity and ophthalmology examination are all in normal condition. ConclusionEyelid trauma with foreign bodies must undergo a complete examination. A good prognosis and outcomes can be achieved when appropriate medical and surgical treatment is performed.